Caribbean Export outlook 2016-2017 (Caribbean Export St. MichaelBB, 2015)
Provides market information on trade and exports. Focuses on the interest in Cuba and China as potential markets and key sectors such as agribusiness (primarily cocoa), creative industries (especially music), renewable energy, financial services and speciality tourism (mainly medical tourism).
Keywords: TRADE